The critical few : energize your company's culture by choosing what really matters - Katzenbach, Jon R., 1932- (BK business book., 2018)
"From one of the founders of the organizational culture movement, and the author of the seminal The Wisdom of Teams (over 400,000 sold worldwide), a book that focuses on the key elements every leader can tap to transform company culture. Every organization has a unique culture, but they all have one thing in common. Whenever they have a big change to make, powerful emotional forces in their culture appear, at first, to resist it. But there are other culture forces under the surface that can be potential sources of catalytic strength. The best leaders succeed by tapping those "critical few" sources. Using an unusual, dialogue-based approach, Katzenbach shows how a sharp focus on just these elements reduces complexity and enables leaders to create profound cultural transformation and positive, lasting impact on performance. The critical few elements are: The critical few traits: the shared characteristics that are at the heart of people's emotional connection to what they do. The critical few behaviors: people's actions that would lead a company to succeed if they were replicated at greater scale. The critical few people: individuals whose emotional intuition and institutional trust make them valued guides for transformation, wherever they are on the org chart"--